2022
DOI: 10.47814/ijssrr.v5i6.412
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Rape in the Mankweng Policing Areas of Limpopo Province, South Africa

Abstract: The purpose of this study was to explore the community members’ perceptions on the nature of rape in the selected Mankweng policing areas of Limpopo Province, South Africa, namely: Mentz, Ga-Makanye and Ga-Thoka. The qualitative research approach was followed, coupled with the Q-methodology research design and exploratory research objective. About 30 participants were purposively sampled to form part of the Three (03) Focus Groups Discussions (FGDs), consisting of 10 targeted groups, this was aided by the revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In this study, health professionals who reported a staff shortage were 0.535 times (AOR = 0.535, 95% CI: 0.319, 0.896) less likely to have good time management practices than those who said there were an adequate number of healthcare professionals at the hospital. This finding is in agreement with a study done at Mankweng Hospital, South Africa in which 47% of respondents strongly agreed that a staffing deficit resulted in poor time management, which ultimately results in poor patient care (8). The likely reason might be that a lack of adequate staff forces employees to work under pressure.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, health professionals who reported a staff shortage were 0.535 times (AOR = 0.535, 95% CI: 0.319, 0.896) less likely to have good time management practices than those who said there were an adequate number of healthcare professionals at the hospital. This finding is in agreement with a study done at Mankweng Hospital, South Africa in which 47% of respondents strongly agreed that a staffing deficit resulted in poor time management, which ultimately results in poor patient care (8). The likely reason might be that a lack of adequate staff forces employees to work under pressure.…”
Section: Discussionsupporting
confidence: 90%
“…Time management is how time is planned, controlled, and utilized and is essential in healthcare organizations (7,8). Effective time management is vital for providing high-quality healthcare because patients wait for less, colleagues and other health workers feel less job-related stress, and activities are completed quickly without interfering with the work of others (9).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations